Answer:
We conclude that the point (-3, 0) does NOT satisfy the inequality.
Explanation:
Given the expression
![y\ge \:\left|x\right|+3\:\:\:\:](https://img.qammunity.org/2022/formulas/mathematics/college/h7xrqwgmenh22xlqi2m4o10ffe0bpt3yjb.png)
putting x = -3 and y = 6
![6\ge \left|-3\right|+3\:\:\:](https://img.qammunity.org/2022/formulas/mathematics/college/riceglcx34kvusphpu3o0rf52oyvh69xk3.png)
Apply absolute rule: |-a| = a
![6\ge \:6](https://img.qammunity.org/2022/formulas/mathematics/college/x42frh4e4b05oa017ndrm8v0jlxtjff1mf.png)
TRUE
Thus, the point (-3, 6) satisfies the inequality.
Given the expression
![y\ge \:\left|x\right|+3\:\:\:\:](https://img.qammunity.org/2022/formulas/mathematics/college/h7xrqwgmenh22xlqi2m4o10ffe0bpt3yjb.png)
putting x = 0 and y = 4
![4\ge \left|0\right|+3](https://img.qammunity.org/2022/formulas/mathematics/college/qzqx36eg8s4uuspk4weozrrpvm7uwvsuk4.png)
Apply absolute rule: |a| = a, a≥0
![4\ge \:3](https://img.qammunity.org/2022/formulas/mathematics/college/wqejvwlh8eq8sgi6zicevf7bpgywb0gto2.png)
TRUE
Thus, the point (0, 4) satisfies the inequality.
Given the expression
![y\ge \:\left|x\right|+3\:\:\:\:](https://img.qammunity.org/2022/formulas/mathematics/college/h7xrqwgmenh22xlqi2m4o10ffe0bpt3yjb.png)
putting x = -3 and y = 0
![0\ge \left|-3\right|+3\:\:\:](https://img.qammunity.org/2022/formulas/mathematics/college/uqg9wj5t11o53gknchcnyf0y3n0wghqc71.png)
Apply absolute rule: |-a| = a
![0\ge \:6](https://img.qammunity.org/2022/formulas/mathematics/college/42w1rg69w81hroirs1whs5qpl28v2263wz.png)
FALSE
Thus, the point (-3, 0) does NOT satisfy the inequality.
Therefore, we conclude that the point (-3, 0) does NOT satisfy the inequality.